PEMBERDAYAAN SISWA SD II SESETAN DALAM MENGURANGI KASUS PENYAKIT DEMAM BERDARAH DI KELURAHAN SESETAN DENPASAR 2012 - Lubis, D. S.; Wati, N. K Eka; Purnama, S. G.; Adhi, K. Tresna; Suariani, P. (Buletin Udayana Mengabdi; Vol 12 No 1 (2013): Jurnal Udayana Mengabdi, 2013)
This community service was conducted in SD N II Sesetan, Denpasar on 13 August 2012. The participants of this activity were 60 students from SD N II grade V Denpasar. Health education about the life span of dengue fever mosquito and the common environment of the mosquito was delivered to the students. After being studied in the class, the activity was continued by identification of jentik at the field. The aims of this activity are to strengthen the role of students in reducing dengue fever cases in Sesetan village. Result of the pre-test and post test showed an increase in knowledge of the students about dengue fever to overcome this disease. Statistical analysis showed a significant differences (P<0.05) between pre-test and post test. Students were asked to identify potential container of mosquite which may be bred at home. There were 221 containers examined by students, and 26% of the containers have larva. It can be concluded that this activity can improve knowledge about dengue fever and larva identification skill. This activity might become a good example to initiate elementary school based program to eradicate dengue fever cases in Sesetan Village. It is recommended to scale up this activity to other school in order to strengthen the role of students in dengue fever prevention approach in Sesetan Village.